XCSL: XML constraint specification language - Jacinto, Marta Henriques (2002)
After being able to mark-up text and validate its structure according to a document's type specification, we may start thinking it would be natural to be able to validate some non-structural issues in the documents. This paper is to formally discuss semantic-related aspects. In that context, we introduce a domain specific language developed for such a purpose: XCSL. XCSL is not just a language, it is also a processing model. Furthermore, we discuss the general philosophy underlying the proposed approach, presenting the architecture of our semantic validation system, and we detail the respective processor. To illustrate the use of XCSL language and the subsequent processing, we present a case-study. Nowadays, we can find some other languages to restrict XML documents to those semantically valid - namely Schematron and XML-Schema. So, before concluding the paper, we compare XCSL to those approaches.